Ultrathin Graphene–Protein Supercapacitors for Miniaturized Bioelectronics. Issue 17 (9th May 2017) - Mosa, Islam M.; Pattammattel, Ajith; Kadimisetty, Karteek; Pande, Paritosh; El‐Kady, Maher F.; Bishop, Gregory W.; Novak, Marc; Kaner, Richard B.; Basu, Ashis K.; Kumar, Challa V.; Rusling, James F.
Abstract : Nearly all implantable bioelectronics are powered by bulky batteries which limit device miniaturization and lifespan. Moreover, batteries contain toxic materials and electrolytes that can be dangerous if leakage occurs. Herein, an approach to fabricate implantable protein‐based bioelectrochemical capacitors (bECs) employing new nanocomposite heterostructures in which 2D reduced graphene oxide sheets are interlayered with chemically modified mammalian proteins, while utilizing biological fluids as electrolytes is described. This protein‐modified reduced graphene oxide nanocomposite material shows no toxicity to mouse embryo fibroblasts and COS‐7 cell cultures at a high concentration of 1600 µg mL −1 which is 160 times higher than those used in bECs, unlike the unmodified graphene oxide which caused toxic cell damage even at low doses of 10 µg mL −1 . The bEC devices are 1 µm thick, fully flexible, and have high energy density comparable to that of lithium thin film batteries. COS‐7 cell culture is not affected by long‐term exposure to encapsulated bECs over 4 d of continuous charge/discharge cycles. These bECs are unique, protein‐based devices, use serum as electrolyte, and have the potential to power a new generation of long‐life, miniaturized implantable devices. Abstract : Commercial implantable bioelectronics are currently powered by bulky batteries which limit device miniaturization and lifespan. Herein, an approach to fabricate ultrathin implantable protein‐based bioelectrochemical capacitors (bECs) which utilize biological fluids and cell culture media as electrolytes with no toxic effects on living cells is described. These bECs have the potential to power a future generation of long‐life, miniaturized implantable biomedical devices.